Development of Interactive Learning Multimedia Reading Early Children's Beginning - Ostawati Gultom; Anita Yus; Sriadhi Sriadhi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Development of Interactive Learning Multimedia Learning Beginning for early childhood (5-6 years) in Christian Kindergarten 3 District Medan Kota, Medan City. Postgraduate Basic Education Study Program, State University of Medan. The purpose of this research and development was to determine the feasibility and effectiveness of interactive learning multimedia for early childhood reading in Group B TK Nasrani 3, Medan Kota District, and Medan City. The development model in this study refers to the 4D (Four-D) researches and development model which consists of 4 main stages, namely define, design, develop, and disseminate. The subjects in this study were 3 expert validators and 20 students of Group B TK Nasrani 3 Medan. The product of this research is a multimedia interactive learning software product on the material of celestial objects for group B students TK Nasrani 3 Medan. The results showed that (1) the feasibility level of interactive multimedia learning pre-reading based on: a) the validation results of the material experts on the feasibility of content by instructional media experts by 3.6, learning material experts by 3.7, while design experts 3.5 in the category with " very worthy ”. b) The practical results of the teacher state that children get very good responses and responses. This can happen because the steps loaded in multimedia learning have instructions and are easily understood by children. 2) the results of the effectiveness of interactive learning multimedia that were developed showed the average result of reading the beginning of the child on the results of initial observations was 45%, which means the child began to develop and the result of the final observation was 83%, which means that the child developed very well.